Reflexiones sobre demografía y formación académica. Conversatorio con egresados de El Colegio de México - Quilodrán, Julieta; Gayet, Cecilia; Goldani, Ana María (El Colegio de México A.C., 2025)
The purpose of this report is to offer an overview of the perspectives of demography specialists who graduated from El Colegio de México regarding their experiences during their training as students, the usefulness of their studies in their professional development, and their reflections on emerging issues in the field of demography.